Specification for bursting discs and bursting discs devices (BSI, 1984)
Bursting discs, Corrosion protection, Gas pressure vessels, Safety devices, Burst tests, High-pressure tests, Gas flow, Pressure vessels, Marking, Fluid pressure, Pipework systems, Installation, Vacuum devices, Safety valves, Flow rates, Gases, Pressure regulators, Thermodynamic properties, Dome shape, Viscosity, Holding, Dynamic viscosity, Supports, Error correction